Efektifitas Promosi Kesehatan Media Video dan Leaflet terhadap Tingkat Pengetahuan tentang Pencegahan Osteoporosis - Setiani, Ditya Yankusuma; Warsini, Warsini (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2020)
The incidence of fractures in the female sex at the age of 95-99 years is 1680 cases and the lowest at the age of 40-44 years is as many as 8 cases (Kemenkes RI, 2015). The fracture incident is the impact of osteoporosis suffered. Osteoporosis is more often found in older people, especially in women after menopause. This makes it important to know more effective promotional media to increase knowledge about osteoporosis prevention in pre-menopausal women. The purpose of this study was to determine the differences in the effectiveness of health promotion using video media and leaflet media on the level of knowledge about osteoporosis prevention in pre-menopausal women. The research design used was quasy experimental with pre test and post test control group design. The respondents of this study were 48 people, 24 for the intervention group using a media extension in the form of video and 24 for the control group using leaflet media. Analysis with Mann-Whitney obtained the results of the average rating of the control group (15.42) lower than the intervention group (33.58) with a significance value of 0.001 (<0.05). Research conclusions that video media is more effective for increasing knowledge about osteoporosis prevention compared to leaflet media